Effect of pre-embedded adhesion failures and surface ply delaminations on the structural integrity of adhesively bonded single lap joints made with curved laminated FRP composite panels. (July 2021) - Behera, Ranjan K.; Parida, S.K.; Das, R.R.
Abstract: This paper investigates fracture mechanics based design of the adhesively bonded Single Lap Joint (SLJ) made with curved Fibre Reinforced Plastic (FRP) composite adherends having pre-embedded adhesion failures and surface ply delaminations at either end of the lap portion. The propagation of pre-embedded through-the-width delaminations and adhesion failures in the SLJ under uniaxial tensile load has been characterized by computing the Strain Energy Release Rates (SERR) near the adhesion failure/delamination fronts. The Virtual Crack Closure Technique (VCCT) has been used for the computation of SERR. Three Dimensional (3-D) non-linear Finite Element (FE) analyses of the SLJ have been carried out for these defects existing either individually or simultaneously at different locations. The predominant modes of failure, the radial location from where these defects may start to grow have been identified. The propagations of adhesion failures have been studied at the interfaces of the adhesive and the adherends by pre-embedding them in the region of high-stress concentrations. Similarly, the propagations of the delaminations are investigated by pre-embedding them beneath the surface ply of both the adherends at the vicinities of the overlap ends. The vulnerabilities of these damage fronts are compared at different locations in the joint for the overall assessment of the structural integrity of the SLJ. The longitudinal shearing mode of adhesion failure is the dominant mode irrespective of their position. The adhesion failure in the lap adherend is more detrimental than the adhesion failure pre-embedded in a similar location at the interface of the strap adherend with the adhesive. The influence of the locations of delaminations when they grow in size on the structural integrity of the joint has also been analysed. The maximum values of SERRs and their radial locations in all the delamination fronts at several locations have been pointed out for structural design purposes. The dominating mode of failure in delamination fronts is highly sensitive to their locations. The growth rates are found to be significantly different in the lap and the strap adherends even for similar locations. It has been observed that the initially straight damage front will gradually tend to be curved in shape.